IDENTIFIKASI DAN PREVALENSI PARASIT YANG MENYERANG LOBSTER (Panulirus sp.) DI KOTA BANDA ACEH CITY - Safrina, Fani; Diana, Farah; Kalsum, Umi; Saputra, Fazril; Zulfadhli, Zulfadhli; Samuki, Khairul (Universitas Teuku Umar, 2022)
Lobster (Panulirus sp.) is a crustacean group widely cultivated in Indonesia because of its high selling value. However, there are several obstacles in lobster cultivation, including infection with various diseases, such as infection with parasites. This research needs to be conducted to determine the types of parasites that infect lobsters (Panulirus sp.) and the prevalence and intensity of parasites found in lobsters at the Ulee Lheu KJA location, Banda Aceh. Parasite identification was carried out at the Fish Quarantine Station for Quality Control and Safety of Aceh Fishery Products, Blang Bintang Aceh Besar. The method used in this study was a survey method, and the lobster sampling technique was carried out randomly. The results of this study show that the results of identification and calculation of the prevalence and intensity of parasites in lobsters (Panulirus sp.) which attack the gills, walking legs, swimming legs, tail, and intestines that have been carried out, it can concluded that two species of parasites attack lobsters, namely Octolasmis sp. and Nemathelminthes with the highest prevalence value in the gills and walking legs in KJA 1 with a total value of 30%, the lowest prevalence value is in the swimming leg organs and intestines in both KJA with a total value of 10%. The highest intensity value was found in the gills of KJA 2 with a total value of 25.5 and/head, and the lowest intensity value was in the swimming leg and intestine organs with a total value of 1 and/head.